Experimental and computational study of melting phase-change material in a triplex tube heat exchanger with longitudinal/triangular fins. (October 2017) - Abdulateef, Ammar M.; Mat, Sohif; Sopian, Kamaruzzaman; Abdulateef, Jasim; Gitan, Ali A.
Highlights: Three heat-transfer enhancements to the PCM melting were experimentally investigated. Longitudinal and triangular fins model in the TTHX were numerically studied. The changes in the mass flow rates on the PCM average temperature were investigated. External triangular fins model was the most efficient for shorter PCM melting time (193 min). Abstract: This study designed, tested, and evaluated an experimental energy storage system that uses a horizontal triplex tube heat exchanger (TTHX) with internal longitudinal fins incorporating phase-change material (PCM), with melting point in the range of 78.15–82.15 °C. The PCM did not entirely melt within the charge time (4 h) for the inside heating at 97 °C. The PCM melting for both-sides heating was successfully accomplished at 90 °C in lesser time than the outside heating method. The changes in the mass flow rates of 16.2, 29.4, and 37.4 min/kg on the PCM average temperature in the axial direction were investigated. The mass flow rate for the non-steady state at 29.4 kg/min consumed a short time to achieve PCM melting, compared with the 16.2 and 37.5 kg/min with different charging temperatures. However, two-types of extended surfaces, namely the longitudinal and triangular fins, were studied numerically. A significant enhancement was achieved using internal, internal-external, and external triangular fins at 11%, 12%, and 15% respectively, compared with the cases with longitudinal fins. Therefore, the external triangular finned tube has been considered the most efficient for the brief melting of PCM (193 min). The total energy stored capacities for the PCM with longitudinal and triangular fins were compared. The simulation agreed well with the experimental results.